Pengembangan Media Pembelajaran Video Animasi Berbasisi Kinemaster Pada Materi Gaya Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas IV SD - Hadi Saifuddhin; Desty Dwi Rochmania (IJPSE : Indonesian Journal of Primary Science Education, 2023)
The problems faced in the world of education today are not only about the lack of use of learning media in the teaching and learning process, but rather the process of learning activities which is the main problem that arises today. The objectives to be achieved in this study are (1) to describe the process of developing kinemaster-based animation video media on style material to develop critical thinking skills of fourth-grade elementary school students and (2) to determine the quality of developing kinemaster-based animated video learning media on style material to develop critical thinking skills of fourth-grade elementary school students (3) to determine the implementation of the development of kinemaster-based animation video media on style material to improve critical thinking skills of fourth-grade elementary school students. This research is classified as development research or (R & D). The development model used in the research is the ADDIE approach. The stages in the ADDIE model, according to (Sugiono, 2015, p. 200), consist of analysis (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). The results of the research indicate that the kinemaster-based animation video learning media is very feasible to use in the learning process. Based on the validator's assessment results, the kinemaster-based animation video learning media obtained very valid results with an average value of 94%. The results of the implementation of animated video learning media on students are 93%, which can be categorized in the perfect category and suitable for use in the learning process. Keywords: Animated video, kinemaster, Critical Thingking